2014
DOI: 10.1063/1.4883901
|View full text |Cite
|
Sign up to set email alerts
|

A high frequency resonance gravity gradiometer

Abstract: A new setup OGRAN--the large scale opto-acoustical gravitational detector is described. As distinguished from known gravitational bar detectors it uses the optical interferometrical readout for registering weak variations of gravity gradient at the kilohetz frequency region. At room temperature, its sensitivity is limited only by the bar Brownian noise at the bandwidth close to 100 Hz. It is destined for a search for rare events--gravitational pulses coincident with signals of neutrino scintillator (BUST) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…It was shown that readout noises can be reduced to this level and even more if one will use the laser pump with 100 W instead of 1 W as it was taken in our estimates. The reason of considering such variant of modernization lays of course in a realistic view on a reconstruction of the existing OGRAN chamber [1,2] into nitrogen cryostat. For helium cryostat version it will require a construction of completely new setup very expensive in creation and exploiting [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that readout noises can be reduced to this level and even more if one will use the laser pump with 100 W instead of 1 W as it was taken in our estimates. The reason of considering such variant of modernization lays of course in a realistic view on a reconstruction of the existing OGRAN chamber [1,2] into nitrogen cryostat. For helium cryostat version it will require a construction of completely new setup very expensive in creation and exploiting [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The "read out" arm of the OGRAN setup containing the discriminator cavity remains under room temperature. In general, a variation of the optical resonator length l leads to the change of the resonance frequency ν according to the simple relation ∆ν = (∆l/l)·ν, i.e., the effect is stronger for the shorter resonator (in the OGRAN setup, L=2 m and l=50 cm [1,2]). On the other hand, a discrimination of the frequency shifts will be better with a narrow resonator bandwidth.…”
Section: Ogran Read Out Arm and Influence Of Discriminator Noisesmentioning
confidence: 99%
See 1 more Smart Citation
“…The deviation from the inhomogeneity are of the post-Newtonian order of magnitude, δρ/ρ GM ⊕ /c 2 R ⊕ 7 × 10 −10 , and are practically unmeasurable in local experiments. Nonetheless, the relativistic effects in the normal gravity field produced by such a density inhomogeneity over the global scale might be noticed in precise measurements of the gravity field conducted with the next generation of gravimeters [57,58] and/or gravity gradientometers [59][60][61]. Thus, we again has to compromise between two models of the Earth's interior -a non-homogeneous density distribution of matter inside a reference level ellipsoid or a homogeneous density with the small, post-Newtonian deviations of the reference level surface from the precise ellipsoid of revolution.…”
Section: Post-newtonian Metricmentioning
confidence: 99%
“…It consists in a search for Galactic collapsing stars on the neutrino channel. In this paper, we describe the present status of opto-acoustical gravitational antenna OGRAN 11 constructed for a multi-channel mode monitoring relativistic events and located the deep underground of Baksan Neutrino Observatory (BNO) close to the Baksan Underground Scintillator Telescope (BUST).…”
Section: Introductionmentioning
confidence: 99%